15 Years of Pension Reform in Germany: Old Successes and New Threats - Holger Bonin (Institute for the Study of Labor (IZA), 2009)
The paper surveys the state of German pension system after a sequence of reforms aimed at achieving long-term sustainability. We argue that the latest reforms have moved pension provision in Germany in principle from a defined benefit to a defined contribution scheme, and that this move has stabilized pension finances to a large extent. We furthermore argue that the real economy consequences of the global financial crisis create threats to the core success factors of the reforms cutting pension levels and raising mandatory pension age. Finally the paper discusses further possible reform measures, including the option to install a fourth pillar providing income in retirement through working after pension age.
Keywords: H55; J11; 330; pension financing; financial crisis; fiscal sustainability survey; Germany; Gesetzliche Rentenversicherung; Rentenreform; Rentenfinanzierung; Nachhaltigkeit; Finanzkrise; Finanzkrise; Deutschland